EDUCATION SPENDING STRATEGY TO ACHIEVE SUSTAINABLE HUMAN DEVELOPMENT: FUTURE VISIONS (American Journal of Business Management, Economics and Banking, 2024)
Among the government institutions concerned with achieving sustainable human development is the Education Institution. Through universities, colleges, institutes and its other branches, it contributes in a qualitative and unique way to preparing human cadres capable of producing and disseminating scientific and technological knowledge through developmental research and educational programs. It is the only institution concerned with Providing other government institutions and sectors with the human expertise necessary to achieve sustainable development, so the financial, material and logistical resources allocated to education through government spending is an urgent necessity. It is noted that the interest of developed countries in providing adequate financial resources to the educational institution has increased its performance and the achievement of goals. However, in Iraq and most developing countries, a decrease in financial allocation to education has been observed despite the amount of financial resources it possesses. This has led to a failure to improve the reality of education and a decline in sustainable human resources. By reviewing the financial allocations directed to education in the tripartite budget (2023-2025), a significant decrease was recorded in the financial allocations to the education sector compared to the previous three years (2020-2022), which hurt the production of human resources that support the Iraqi economy to achieve sustainable development, so Iraq ranked (121) in the global classification of levels of sustainable human development. The research aims to analyze the effectiveness of government support through spending on education in Iraq from (2010-2025) and its impact on achieving sustainable human development, by adopting the descriptive analytical approach.